UMPSA Young Scientists achieve International Recognition at Microbiome Summit 2025 - Hajar Fauzan, Ahmad (UMPSA, 2025)
HONG KONG, 11 January 2025 – Research conducted by postgraduate students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) won the Best Research Abstract Award and Best Poster Presentation Award at the Microbiome Summit 2025.